FIKIH EKOLOGI: FORMULASI FIKIH UNTUK PELESTARIAN LINGKUNGAN MELALUI PENDEKATAN MAQASID SYARIAH - Faza, M Dzikrullah (Universitas Islam Madura, 2024)
Humans with more practical, hedonistic, or sekuler lifestyles tend to view the world differently than those who do not. Conventional wisdom around water is usually refined during economic development. In addition, Arabic has become a catchphrase that conveys the idea that in the modern period, people must respect their financial needs in order to live. All relevant parties, including the religious community, should take note of this issue and participate in its resolution. Religion serves as a tool to address crisis points in society that are not only related to technology but also to the spirit and values of those who use it. The purpose of this study is to examine the fundamental issues of the natural disaster via the lens of a finger. Researchers are eager to learn how Islamic beliefs about the environment might be transformed into Islamic ecological concepts. In this context, developing an ecological theory of human behavior is crucial to creating a new paradigm in fiqh. This research is conducted using a library research methodology that integrates normative and philosophical theory as well as data collection techniques such as doing a literature analysis. The research findings indicate that humans have a duty to protect the environment since they are the kholifah of the earth and should be pristine for the environment. According to normative standards, environmental management is considered a component of maqashid al-syari'ah in the form of hifz al-bî'ah and serves as a mediator for the execution of the obligation of kulliyat al-khamsah, making it obligatory to be carried out as well. Therefore, in the pendekatan sadd al-zarâ'I, it is necessary to monitor and address any activities that may result in kerusakan. Islam forbids the establishment of conservation zones similar to those described by Prophet Muhammad.